PENGEMBANGAN APLIKASI MARKETPLACE INFLUENCER SEBAGAI MEDIA PROMOSI UMKM - Chabelita ananda Putri; Suyud Widiono (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The endorsement strategy is an effective digital marketing method for expanding reach and increasing consumer trust. However, this practice is still dominated by large brands collaborating with well-known influencers, thus limiting access to affordable promotions for Micro, Small, and Medium Enterprises (MSMEs). On the other hand, micro-influencers with smaller audiences lack a structured, professional platform for collaborating with MSMEs. This study aims to develop a mobile-based influencer marketplace application that facilitates integrated collaboration between MSMEs and influencers. The development method used is the Waterfall method, which includes needs analysis, system design, implementation, testing, and maintenance. The mobile application was developed to support MSMEs in delivering products, receiving influencer offers, and placing endorsement orders through a digital transaction system. The development results show that the developed marketplace application provides paid endorsement features as well as additional free endorsement features (product barter), enabling more flexible, transparent, and mutually beneficial collaborations. Therefore, this application has the potential to be an initial solution in expanding digital promotion opportunities for MSMEs and supporting more inclusive collaboration with micro-influencers.